Systematic Literature Review: World Oil Commodity Price Fluctuations Financial Accounting Perspective - Elita Septemberiyanti; Ryani Virliana Muliawan; Rahma Agustria; Amanda Ayu Ramadhani; Rika Henda Safitri; Tertiarto Wahyudi; Ruth Samantha Hamzah (International Journal of Multidisciplinary Sciences and Arts, 2025)
Global oil price volatility creates complex challenges for the transparency of financial reporting of national energy companies, especially PT Pertamina as a strategic state-owned enterprise that faces double accountability pressure to shareholders and the public. This study aims to analyze the influence of fluctuations in world oil commodity prices on the transparency of PT Pertamina's financial statements from a financial accounting perspective through a systematic literature review approach. The PRISMA 2020 method was applied to review 16 reputable journals for the 2020-2025 period selected from 309 initial articles through the Scopus, Web of Science, and Google Scholar databases. The results of the study revealed that oil price volatility had a significant impact on net profit fluctuations, the complexity of exchange rate differences, and the decline in financial health for the 2016-2020 period. PT Pertamina's transparency shows improvements through the implementation of ISO 37001 and GRI Standards 2021, but still faces the challenges of weak ethical principles, inconsistency of PSC regulations, and performance gaps with global competitors. The research recommends comprehensive governance reforms, business diversification, regulatory harmonization, and strengthening supervision to improve the credibility of financial reporting in the face of global market dynamics.